Genetically predicted alterations in thyroid function are associated with the risk of benign prostatic disease - Huang, Yan; Chen, Cheng; Zhou, Wanqing; Zhang, Qian; Zhao, Yanfei; He, Dehao; Ye, Zhi; Xia, Pingping (Frontiers in Endocrinology, 2023)
Background Benign prostatic diseases (BPDs), such as benign prostate hyperplasia (BPH) and prostatitis, harm the quality of life of affected patients. However, observational studies exploring the association between thyroid function and BPDs have hitherto yielded inconsistent results. In this study, we explored whether there is a causal genetic association between them using Mendelian randomization (MR) analysis. Methods We used publicly available summary statistics from the Thyroidomics Consortium and 23andMe on thyrotropin (TSH; 54,288 participants), thyroxine [free tetraiodothyronine (FT4); 49,269 participants], subclinical hypothyroidism (3,440 cases and 49,983 controls), overt hypothyroidism (8,000 cases and 117,000 controls), and subclinical hyperthyroidism (1,840 cases and 49,983 controls) to screen for instrumental variables of thyroid function. Results for BPD such as prostatic hyperplasia (13,118 cases and 72,799 controls) and prostatitis (1,859 cases and 72,799 controls) were obtained from the FinnGen study. The causal relationship between thyroid function and BPD was primarily assessed using MR with an inverse variance weighted approach. In addition, sensitivity analyses were performed to test the robustness of the results. Results We found that TSH [OR (95% CI) = 0.912(0.845-0.984), p =1.8 x 10-2], subclinical hypothyroidism [OR (95% CI) = 0.864(0.810-0.922), p =1.04 x 10-5], and overt hypothyroidism [OR (95% CI) = 0.885 (0.831-0. 944), p =2 x 10-4] had a significant effect on genetic susceptibility to BPH, unlike hyperthyroidism [OR (95% CI) = 1.049(0.990-1.111), p =1.05 x 10-1] and FT4 [OR (95% CI) = 0.979(0.857-1.119), p = 7.59 x 10-1] had no effect. We also found that TSH [OR (95% CI) =0.823(0.700-0.967), p = 1.8 x 10-2] and overt hypothyroidism [OR (95% CI) = 0.853(0.730-0.997), p = 4.6 x 10-2] significantly influenced the prostatitis, whereas FT4 levels [OR (95% CI) = 1.141(0.901-1.444), p = 2.75 x 10-1], subclinical hypothyroidism [OR (95% CI) =0. 897(0.784- 1.026), p = 1.12 x 10-1], and hyperthyroidism [OR (95% CI) = 1.069(0.947-1.206), p = 2.79 x 10-1] did not have a significant effect. Conclusion Overall, our study results suggest that hypothyroidism and TSH levels influence the risk of genetically predicted BPH and prostatitis, providing new insights into the causal relationship between thyroid function and BPD.